Fostering Entrepreneurial Interest: An Analysis of the Role of Entrepreneurship Education and Skills Competence - Nurryna, Ayu Fiska; Widiastusi , Indah; Saputro, Herman (Universitas Pendidikan Ganesha, 2025)
Many vocational students have low interest in entrepreneurship, despite having Entrepreneurship Education in the curriculum. It is important to understand the factors that influence entrepreneurial interest, including the role of Entrepreneurship Education and Expertise Competencies. This study aims to analyze the effect of Entrepreneurship Education and Expertise Competencies on entrepreneurial interest of vocational students, both individually and simultaneously. This research uses a quantitative design. The research subjects involved in this research are vocational students selected through cluster sampling technique totaling 211 students. The data collection method used is a questionnaire. The instrument used was a validated questionnaire sheet, and the data were analyzed using linearity test, ANOVA, and regression analysis to see the effect of independent variables on the dependent variable. The results showed that Entrepreneurship Education has a significant influence on students' entrepreneurial interest, while Expertise Competency has no significant effect individually. However, when analyzed simultaneously, these two variables show a significant influence in increasing entrepreneurial interest. In addition, significant differences were found in entrepreneurial interest among different skill groups. This study concludes that the integration between Entrepreneurship Education and Skill Competency in SMK curriculum is important to increase students' entrepreneurial interest. Future research is recommended to expand the geographical coverage and sample for greater validity as well as examine other variables that could potentially affect entrepreneurial interest.